Long-Term Population Stability in the Greater Red Hills Region Amidst Range-Wide Declines: A Case for Integrated Management - Theron M. Terhune II; D. Clay Sisson; William E. Palmer; Shane D. Wellendorf (National Quail Symposium Proceedings, 2017)
All natural habitats possess inherent conservation value, including the presence of rare or endemic species, provision of ecosystem services, historic landmarks, or resources harvested. Large-scale loss of natural habitats and deterioration of fire-mediated habitats has caused precipitous declines of native fauna and flora in the southeastern US. The role of private landholdings in wildlife and conservation is often underestimated, and consumptive use of wildlife is commonly viewed as counterproductive to sustainability. However, in the Greater Red Hills region (GRH) of north Florida and south Georgia, intentional management for northern bobwhite (Colinus virginianus) on private lands has not only created ‘‘huntable’’ and sustainable bobwhite populations but also enhances overall conservation value among working landscapes – the overall estimated economic value of the GRHs properties is 272 million. Despite range-wide population declines in bobwhite abundance, proper application of frequent fire combined with sound forest management has yielded bobwhite densities of 4-8 bobwhites/ha. This intentional and intensive management has facilitated preservation of ecosystem integrity and profited numerous declining, threatened or endangered species. Thus private lands, which encompass two-thirds of the US, are critically important for maintaining biotic diversity and wildlife populations. Many conservation action plans (e.g., NBCI) underscore the importance of public lands, but few have quantified the conservation value of private lands intentionally managed for bobwhites. Yet, pressures are mounting for many private landowners to balance costs and benefits of management, and more effectively operate with fewer dollars. In many cases, lands not economically competitive for wildlife may shift toward agricultural, industrial, or residential uses in the future, diminishing the natural conservation value of these lands. Incentivizing private lands conservation (i.e., providing dollars, tax breaks) and strategically leveraging these landscapes as conservation centers may improve stability of bobwhites and other species in these regions, and expedite population expansion to surrounding areas.
Keywords: biodiversity; colinus virginianus; conservation; Greater Red Hills; private land; northern bobwhite; value; working lands